145k views
2 votes
9m^2 - 49factor each expression. Be sure to check for the greatest common factor first.

User Teaqu
by
6.0k points

1 Answer

2 votes

We need to factor the following polynomial:


9m^2-49

We can see that:


9m^2=3^2m^2=(3m)^2

And


49=7^2

Then, we can use the following factor rule:


x^2-y^2=(x-y)(x+y)

We have that:


x=3m,y=7

Then, we can factor the polynomial as follows:


9m^2-49=(3m)^2-(7)^2=(3m-7)(3m+7)

In summary, we have:


9m^2-49=(3m-7)(3m+7)

User Karlsebal
by
6.2k points